2016
DOI: 10.1177/0899764016651335
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Engagement and Retention

Abstract: The declining number of U.S. volunteers is troubling, necessitating improved understanding of drivers of volunteer retention such as volunteer engagement. We utilized the job demands-resources model to investigate the moderating role of community service self-efficacy (CSSE) on the relationships between two demands (organizational constraints and role ambiguity) and volunteer engagement. Volunteers (N = 235) from three U.S. nonprofit organizations participated in a survey as part of a volunteer program assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Our results advance the literature in the volunteer area by identifying specific antecedents of organization identification. Previous work in the volunteer literature has shown the importance of these variables in leading to engagement [23] and retention [26]. However, studies have not investigated discrete factors which lead to organization identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results advance the literature in the volunteer area by identifying specific antecedents of organization identification. Previous work in the volunteer literature has shown the importance of these variables in leading to engagement [23] and retention [26]. However, studies have not investigated discrete factors which lead to organization identification.…”
Section: Discussionmentioning
confidence: 99%
“…She defines engagement as a psychological state of volunteers marked by affective commitment, positive affectivity, and empowerment. Among volunteers, engagement is shown to affect variables such as self-efficacy [23], satisfaction with volunteer experiences [24], psychological well-being [25], and the intention to remain in organizations [26].…”
Section: Importance Of Organization Identificationmentioning
confidence: 99%
“…In this project, different supporting programmes targeting children at risk of exclusion are implemented; one of which is focused on the implementation of after-school classes that are managed by volunteers. All of these experiences indicate the powerful effects of educational volunteering on different educational levels including adult and children education as well as in the creation of a positive state of mind (Harp, Scherer, & Allen, 2017).…”
Section: Volunteering and Quality Educationmentioning
confidence: 99%
“…In accordance with this need, exacerbated by the continually decreasing trend of volunteerism in the USA (Bureau of Labor Statistics, 2016), previous work has focused largely on concepts that help explain the length of volunteer service, such as satisfaction, organizational commitment, and intentions to quit (Allen & Mueller, 2013; Cnaan & Cascio, 1998; Miller, Adair, Nicols, & Smart, 2014). Recently, volunteer literature has acknowledged the role of engagement as another aspect which may help explain the influence of volunteers' experiences on subsequent attendance outcomes (Alfes, Shantz, & Bailey, 2015; Harp, Scherer, & Allen, 2016; Huynh, Xanthopoulou, & Winefield, 2014; Malinen & Harju, 2016). Other studies have made the case for studying volunteers' work engagement to gain a better understanding of volunteers' performance, about which less is known (Haivas, Hofmans, & Peperman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Alfes et al (2015) similarly found that volunteers' work engagement mediated the relationship between two types of organizational support (i.e., task‐focused and emotion‐focused) and intention to leave their organizations. In contrast to this approach, Harp et al (2016) examined two negative volunteer demands, role ambiguity and various work constraints (e.g., inadequate help from others, poor equipment or supplies, volunteer supervisor, other volunteers, lack of necessary information, etc. ), both of which were associated with volunteer engagement, though it should be noted that some of the items included under the heading of work constraints certainly operationalize a lack of support from the volunteer organization.…”
Section: Introductionmentioning
confidence: 99%